Alternative Approach to Determination of Malaysian Economic Behaviour (International Journal of Banking and Finance, 2016)
This study documents significant findings on the determination of Malaysian economic behaviour in relation to its close trading partners. The data series for this study were from Malaysia, the USA, and China, over a 25-year period. The test procedure incorporated a fully specified Auto Regressive Distributed Lag (ARDL) model with optimum lags being identified from high R-Squared value and the absence of serial correlation. The gross domestic product and industrial production indices were accounted for to re-examine a macroeconomic modelling approach to determination of the Malaysian economy. The results affirmed evidence of significant explanatory role of American and Chinese lagged GDP and IPI in determining the Malaysian economy. Our test results further identified a significant long-run interdependence between Malaysian economy and its major trading partners. In our view, these findings, given the appropriate econometric methodology, suggested significant policy implications concerning the timing and accuracy of risk management practices in preventing economic crisis to occur in Malaysia.